Load characterization on the joints of the A320 engine inlet cowl acoustic panel. (October 2019) - Conceição, Bruno; Anes, V.; Reis, L.
Abstract: Aircraft operate in environments in which the components are subject to large temperature and pressure variations. In aircraft structures such as the engine nacelles, composed by several components and different materials, the presence of wear and corrosion becomes noticeable due to their operation in such environments. Corrective actions must be employed to the components which present this kind of problems. The acoustic panels of the inlet cowl of the Airbus A320/A321, present corrosion problems on the aluminium doublers of the joints. In order to develop a corrective action to the joint of the acoustic panels, the analysis of the mechanical behaviour and forces acting on the joint must be carried out. In this work, a methodology involving Computational Fluid Dynamics, Finite Element Method and Computer Aided Design tools is developed in order to evaluate the mechanical behaviour of the acoustic panels joint. The assessment of the aerodynamic loads acting on the inlet cowl was performed using STAR CCM+ software. The structural analysis of the joint members of the acoustic panels was made with the use of FEM tools in ANSYS Workbench software. The critical steps involved in the analysis are explained. Obtained results are discussed and conclusions are presented. Graphical abstract: Unlabelled Image Highlights: Engineering tools integrated in a real case scenario CAD tools, CFD and FEM analysis are employed Aeronautical components are studied, analysed and evaluated The mechanical behavior of an acoustic panel joints is analysed